STRATEGI GURU GEOGRAFI DALAM PENGGUNAAN MEDIA PEMBELAJARAN PADA PEMBELAJARAN ONLINE - Feri Padli; Rusdi Rusdi; Hendra Hendra (Universitas Negeri Gorontalo, 2022)
This article will reveal strategies for using learning media from Geography teachers during online learning (learning in networks). The aim is to find out what media is used in online geography learning and also the teacher's competence in using Geographic Information System (GIS) media in geography learning. It is hoped that the outcome of the research will be used as an evaluation material and recommendation for the next action in an effort to increase the quantity of relevant media and the quality of learning outcomes of Geography in schools. By planning training in Community Service programs. The data collection method used a special interview system for the main resource person, namely the Geography Teacher by using an online questionnaire for a random sample and secondary data documentation. The results obtained are the class media that is most often used in geography learning the first choice is to use the Whatsapp Group chat application, then Google Classroom and for face-to-face virtual use of video conferencing applications such as zoom or google meet. Meanwhile, the media for teaching teacher material still uses map media, both printed and digital, books or modules, and powerpoint presentations. Meanwhile, GIS applications are still very minimally utilized. The reasons stated are because of the relevance of the material, the easier process if using more general media and the availability of supporting facilities in the agency. However, the perception of his ability to prepare learning media is considered quite good. The only obstacle or challenge is increasing student motivation, and personal self-motivation to work that needs to be improved..